2016
DOI: 10.3905/jpm.2016.42.5.079
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Indeterminate Factor-Based Asset Allocation

Abstract: Asset allocation represents a fundamental strategic decision for every institutional investor.Though many asset allocation approaches have been recommended and implemented in various forms, each has its own strengths and weakness. A careful review of current asset allocation frameworks provided motivation to design a hybrid approach that addresses many of these perceived individual shortcomings. Our guiding principle was to use several familiar elements to create a flexible process that incorporates less-quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The duty of institutional investors has been interpreted strictly in financial terms, fulfilled through the maximization of beneficiaries’ financial interests in excess of industry benchmarks. This primary framework of maximization of returns was perpetuated within organizations through a set of practices and incentive structures focused on managing determinate risks in order to maximize short-term profit (Blyth, Szigety, & Xia, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The duty of institutional investors has been interpreted strictly in financial terms, fulfilled through the maximization of beneficiaries’ financial interests in excess of industry benchmarks. This primary framework of maximization of returns was perpetuated within organizations through a set of practices and incentive structures focused on managing determinate risks in order to maximize short-term profit (Blyth, Szigety, & Xia, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond these considerations, Ang et al (2009) emphasize that the set of factors should be parsimonious, and that factors must have the capacity to be traded in sufficiently large quantities. Taking a more practical perspective, Blyth, Szigety, and Xia (2016) stress that the chosen factors should be able to capture an investor's risk and return objectives and general investment strategy.…”
Section: Empirical Proceduresmentioning
confidence: 99%
“…The “real rates” premium captures the risk of bearing exposure to real interest rate changes and measures the performance of inflation‐linked government bonds relative to nominal government bonds (Greenberg et al, 2016). While AQR (2018) suggest that investors are not equally (if at all) affected by real interest rate risk, other studies have included the real rates premium as a factor in factor‐based portfolios (Bass et al, 2017; Blyth et al, 2016; Clarke et al, 2005; Greenberg et al, 2016). We construct both a US and a global real rates premium as the return of the respective BB inflation‐linked bond index in excess of the risk‐free rate.…”
Section: Empirical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…and suggested a methodology for mapping given factors to asset types. Blyth et al [2016] suggested FIFAA (flexible indeterminate factor-based asset allocation) and flexibly integrated into the Strategic Asset Allocation process with the reasonable view of Investment committee and board of directors with bottom-up analysis across the market. Bass et al [2017] applied the factor-based SAA framework to the portfolios of representative institutional investors.…”
Section: Introductionmentioning
confidence: 99%